Radial Lengthening in the Management of Distal Radius Fractures: A Prospective Study of Clinical and Radiographic Outcomes - Hsiao-Hung Cheng; Chi-Hsiang Hsu; Yu-Der Lu; Hao-Chen Liu; Wen-Chiung Huang; Shan-Ling Hsu (Formosan Journal of Musculoskeletal Disorders)
Background: Distal radius fractures (DRFs) may occur with loss of radial height and compromise the stability of distal radioulnar joint (DRUJ). Radial distraction during volar plating of DRFs had been reported to be a reliable treatment for DRUJ instability and pain relief. Here, we ask if radial lengthening procedure could improve clinical results in DRFs. Objectives: We compared the clinical outcomes of radial lengthening versus conventional anatomic reduction in extra-articular DRFs. Materials and Methods: This prospective, randomized single-center trial included 50 patients with extra-articular DRFs (25 with radial lengthening and 25 with conventional reduction) treated between January 2019 and June 2020. Evaluation was based on radiographic parameter measurements and clinical examination, including the Disabilities of the Arm, Shoulder, and Hand (DASH) score, Patient-Rated Wrist Evaluation (PRWE) score, range of motion, and Visual Analog Scale (VAS). Results: No significant differences were observed in the DASH score, PRWE score, and VAS score at 6 months, or in the clinical radiographic measurements, except for ulnar variance, which was negative in the over-reduction group (P < 0.05). Both groups exhibited radial height loss. Ninety percent of patients in both groups had Palmer Type 1 triangular fibrocartilage complex injury, but none had DRUJ instability requiring further treatment. The two groups were comparable in terms of complications. Conclusions: Radial lengthening had similar clinical results compared with conventional procedure in distal radius fractures. We suggested that radial lengthening is not required routinely in patients with DRFs unless the DRUJ remains unstable after surgery.